Costs and benefits of inter-departmental innovation collaboration - Maarten Cuijpers; Hannes Guenter; Katrin Hussinger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
Inter-departmental innovation collaboration facilitates innovation performance. At the same time, it has been identified as source of increased coordination costs. Using organizational information processing theory, this paper builds and tests hypotheses on the costs and benefits of innovation-related collaboration within firms. Based on a sample of 433 German manufacturing firms we show inter-departmental innovation collaboration to increase process innovation performance, but also to produce costs in terms of project delay and project termination. These costs, however, do not affect innovation performance at the firm level. This finding suggests firms to be well able to balance the costs and benefits of interdepartmental collaboration across their innovation project portfolio. Theoretical and managerial implications are discussed.
urn:nbn:de:bsz:180-madoc-31140
Keywords: O32; M54; O31; 330; Inter-departmental innovation collaboration; innovation performance; project delay; project termination